TRANSFORMATION OF JUNIOR HIGH SCHOOL STUDENTS' MUTUAL COOPERATION BEHAVIOR IN THE MIDST OF SOCIAL CHANGES IN MODERN SOCIETY - Lonta, Usman; Azhar, Muhammad (Journal of Entrepreneur, Business and Management, 2025)
This study examines changes in the behavior of mutual cooperation of junior high school students in the context of modern society characterized by the intensification of the use of digital media and shifts in social interaction patterns. The purpose of the study is to identify the form of change in mutual cooperation behavior, the factors that affect it, and its implications on the quality of adolescent social relations. The research uses a qualitative approach with in-depth interview techniques and observation of students as the main informants, as well as educators as key informants. Data analysis was carried out thematically to capture the dynamics of social meaning that developed in the school environment. The results of the study show that there is a transformation of mutual cooperation behavior from a direct pattern of collective participation to a more individualistic and digital-based form of social engagement. Students tend to build relationships through social media, which on the one hand expands the network of friends, but on the other hand reduces the intensity of face-to-face togetherness and weakens the practice of spontaneous mutual cooperation in the school environment. The findings also show a decrease in social sensitivity and empathy in collective activities, as the orientation to virtual interactions increases. In addition, this change is influenced by the factors of gadget usage habits, peer communication patterns, and the lack of social space that encourages direct cooperation.Sociologically, this condition reflects the process of social modernization that shifts the value of togetherness towards a more pragmatic and instrumental orientation of relationships. This study emphasizes the importance of the role of the educational and family environment in revitalizing the value of mutual cooperation through strengthening collaborative activities and habituating offline social interactions. These findings are expected to serve as a basis for consideration for educators and policymakers in designing social education strategies that are adaptive to the challenges of modern society.Keywords: mutual cooperation, junior high school students, social interaction, modern society, behavior change